Significance (return) in the Holy Quran (Journal of the College of Basic Education, 2022)
In this research, I dealt with the significance of (return) in the Holy Qur’an, and presented it with an introduction to the subject of reversal in linguistic dictionaries, and the difference between reversal and each of the return, reversal, and relegation, as they appear to the reader to be synonymous, but they are in fact different in terms of meaning.I also showed the difference between the verb (return) and (reply) in terms of the Quranic use of them. The term “return” and its derivatives were mentioned in (104) verses of the Holy Qur’an, of which (79) were Meccan verses, and (25) of them were civil verses, and indicated the following meanings:Turning to the thing, repentance, answering the message, taking back the irrevocable divorce and refusing, oud, returning to the world, rain, the return after death, and the threat